Phytochemicals from Dodonaea viscosa and their antioxidant and anticholinesterase activities with structure–activity relationships. (1st September 2016) - Muhammad, Akhtar; Tel-Çayan, Gülsen; Öztürk, Mehmet; Duru, Mehmet Emin; Nadeem, Said; Anis, Itrat; Ng, Seik Weng; Shah, Muhammad Raza
Abstract: Context Dodonaea viscosa (L.) Jacq (Sapindaceae) has been used in traditional medicine as antimalarial, antidiabetic and antibacterial agent, but further investigations are needed. Objective This study determines the antioxidant and anticholinesterase activities of six compounds (1 –6) and two crystals (1A and3A ) isolated from D. viscosa, and discusses their structure–activity relationships. Materials and methods Antioxidant activity was evaluated using six complementary tests, i.e., β-carotene-linoleic acid; DPPH, ABTS +, superoxide scavenging, CUPRAC and metal chelating assays. Anticholinesterase activity was performed using the Elman method. Results Clerodane diterpenoids (1 and2 ) and phenolics (3 –6 ) – together with three crystals (1A, 3A and7A ) – were isolated from the aerial parts of D. viscosa . Compound3A exhibited good antioxidant activity in DPPH (IC50 : 27.44 ± 1.06 μM), superoxide (28.18 ± 1.35% inhibition at 100 μM) and CUPRAC (A0.5 : 35.89 ± 0.09 μM) assays. Compound5 (IC50 : 11.02 ± 0.02 μM) indicated best activity in ABTS assay, and6 (IC50 : 14.30 ± 0.18 μM) in β-carotene-linoleic acid assay. Compounds1 and3 were also obtained in the crystal (1A and3A ) form. Both crystals showed antioxidant activity. Furthermore, crystal3A was more active than3 in all activity tests. Phenol6 possessed moderate anticholinesterase activity against acetylcholinesterase and butyrylcholinesterase enzymes (IC50 values: 158.14 ± 1.65 and 111.60 ± 1.28 μM, respectively). Discussion and conclusion This is the first report on antioxidant and anticholinesterase activities of compounds1, 2, 5, 6, 1A and3A, and characterisation of7A using XRD. Furthermore, the structure–activity relationships are also discussed in detail for the first time.